ANALISIS KOMPARASI KINERJA KEUANGAN PERBANKAN KONVENSIONAL DAN PERBANKAN SYARIAH - Lemiyana Lemiyana (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
Currently there are many Islamic banks in Indonesia as a form of concern for the banking industry with a selection of the bank in accordance with the Islamic shari’a. Many conventional banks began to open Islamic branches, so that the majority of Indonesian people who are Muslim may use the services of the bank without having to fear about riba. Issues addressed in this study is a comparison of the financial performance of Bank Negara Indonesia (Persero) Tbk, Bank Negara Indonesia Syariah, Tbk period 2010 - 2015. The purpose of this study was to compare the financial performance Financial Bank Negara Indonesia (Persero) Tbk, Bank Negara Indonesia Syariah, Tbk period 2010 – 2015. In this study, the method used is the analysis of data and descriptive. The results showed there were significant differences in the financial performance of conventional banks and Islamic banks. However, the overall financial performance of conventional banks and Islamic banks were equally good, because Islamic banks better in the ratio of Liquidity and efficiency ratios, while conventional banks better in solvency ratio.